AKTIVITAS PENGHAMBATAN ENZIM XANTIN OKSIDASE DARI EKSTRAK, FRAKSI, DAN SUBFRAKSI EMPAT TANAMAN SUKU MORACEAE - Rhomlah Jahja, Sitti
Gout is a joint inflammatory disease caused by hyperuricemia or high levels of uric acid in the blood. This condition leads to the deposition of uric acid in the tissue which can induce inflammation. Some plants of Moraceae are traditionally used to treat the gout symptoms, therefore, further research is needed regarding the inhibitory activity of the xanthine oxidase enzyme which acts as a catalyst in the formation of uric acid. This study was conducted in vitro by measuring the decrease of uric acid absorbance using UV spectrophotometer at a wavelength of 290 nm. The decrease of uric acid absorbance indicates the inhibitory activity of the xanthine oxidase enzyme which is expressed in percent (%) inhibition. It was determined from the ethanol extract of breadfruit (Artocarpus altilis (Parkinson) Fosberg.), jackfruit (Artocarpus heterophyllus Lamk.), chempedak (Artocarpus integer (Thunb.) Merr.), and mulberry (Morus alba L.) leaves (at a concentration of 100µg/mL). Ethanol extract with the highest inhibitory activity was fractionated and the highest activity fractions was determined for its IC50 (at a concentration of 100 µg/mL). The fraction was then sub-fractionated and determined for the percent inhibition of each subfraction obtained (at a concentration of 100µg/mL). Results showed that the highest inhibitory activity was found in the breadfruit ethanol extract with percent inhibition of 12.81 ± 0.75 %. The ethyl acetate fraction from breadfruit leaf ethanol extract had the highest activity with% inhibition of 17.16 ± 0.67 % and the IC50 was 938 µg/mL, while IC50 of allopurinol was 1.24 µg/mL. The first spot from subfractionation of ethyl acetate fraction gave the highest activity with percent inhibition of 22.09 ± 0.49%. Based on the results, it was concluded that breadfruit leaves which traditionally used for gout treatment have an inhibitory activity for the xanthine oxidase enzyme.